Radio-cytological diagnosis of nodulocaseous tubercular lymphadenitis: a clinical dilemma - Kaushik, Ankit; Arora, Disha; Kolte, Sachin; Gupta, Kusum; Mandal, A K (Annals of Pathology and Laboratory Medicine, 2015)
Nodulocaseous tubercular lymphadenitis is a rare entity presenting with ill-defined breast lump, accompanied by non-specific systemic presentation. We present a case report of a young female patient presenting with breast lump and no definitive clinical diagnosis. The radiological investigation like ultrasound breast revealed multiple enlarged nodulocaseous lymph nodes in all four quadrants of breast. The presence of epitheloid cell granuloma with necrosis on fine needle aspiration cytology established primary diagnosis of intramammary tubercular lymphadenitis. Nodulocaseous tubercular lymphadenitis breast often presents with atypical presentation and primary diagnosis is often difficult to establish. The case establishes the role of ultrasound breast and fine needle aspiration cytology being rapid and cost effective way of diagnosing this lesion.